CREATION OF A HIGH-PRECISION CALCULATION MODEL OF A THREE-ELEMENT STRUCTURE OF A FREIGHT CAR BOGIE (Transport systems and technologies, 2021)
A 3D model and computational model of a freight car bogie of type 18-100 has been developed. The design model was validated in comparison with the complex of running tests. Calculations were carried out and indicators of strength and fatigue resistance were evaluated for further research. On the basis of the calculations, the probable zones of fatigue accumulation have been established.
Keywords: rolling stock, freight car, supporting structures, strength, model, calculations, CAD.